2019
DOI: 10.1002/jctb.6204
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐induced precipitation of metal ions in aqueous solutions

Abstract: BACKGROUND This work focuses on removing metal ions (Fe3+, Cu2+, and Zn2+) from aqueous solutions and real wastewater by underwater plasma. RESULTS Results show that the joint presence of Fe3+, Cu2+, and Zn2+ are needed for effective precipitation of these ions from aqueous solutions. The short‐time underwater plasma treatment leads to more effective removal of metal ions from real wastewater compared to treatment facilities of a factory. CONCLUSIONS Removing metal ions from aqueous solutions of their mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In the last years, plasma-liquid systems have attracted considerable attention of researchers on a variety of applications domains that include, i.e., environmental and wastewater remediation [7,8], nanomaterial processing [9,10], cancer cells treatment [11], sterilization and disinfection [12], bacterial biofilm prevention and eradication [13] and analytical chemistry [14,15] … etc. In particular, plasma treatment techniques have been tested: i) for the decomposition of many harmful compounds from water, including; herbicide [16], pesticides [17], phenols [7,18], organic dyes [19], As 3+ , Cr 6+ , Fe 3+ , Cu 2+ and Zn 2+ [20,21], biomolecules, Virus and bacterial Inactivation [22][23][24][25], pharmaceuticals [26,4] and veterinary antibiotics [27]; ii) For the possible removing of chemical and biological wastes in all three states; gas, liquid and solid [28]; for the enhancement of biodegradability of coking wastewater [29].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, plasma-liquid systems have attracted considerable attention of researchers on a variety of applications domains that include, i.e., environmental and wastewater remediation [7,8], nanomaterial processing [9,10], cancer cells treatment [11], sterilization and disinfection [12], bacterial biofilm prevention and eradication [13] and analytical chemistry [14,15] … etc. In particular, plasma treatment techniques have been tested: i) for the decomposition of many harmful compounds from water, including; herbicide [16], pesticides [17], phenols [7,18], organic dyes [19], As 3+ , Cr 6+ , Fe 3+ , Cu 2+ and Zn 2+ [20,21], biomolecules, Virus and bacterial Inactivation [22][23][24][25], pharmaceuticals [26,4] and veterinary antibiotics [27]; ii) For the possible removing of chemical and biological wastes in all three states; gas, liquid and solid [28]; for the enhancement of biodegradability of coking wastewater [29].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal salts are commonly found in the wastewater of various industries, including chemical, textile, electroplating, and others. According to Wang et al [135] and Khlyustova et al [136], these salts often contain components of lead, iron, nickel, chromium, iron, cuprum, zinc, and arsenic. The removal of heavy metals from industrial effluent is a crucial aspect of wastewater purification technology.…”
Section: Common Industrial Pollutantsmentioning
confidence: 99%
“…It is only noted that the resulting particles include iron and oxygen (EDX analysis). In [10], the effect of a diaphragm discharge on an aqueous solution of FeCl3 was studied. The authors observed a decrease in the concentration of Fe 3+ ions and the formation of a precipitate a in the region of the diaphragm.…”
Section: Introductionmentioning
confidence: 99%